Finding Guide to the Joss Whedon Collection (Box Listing), Comic Books Only - Evelyn Taylor:::Archivist:::
The Joss Whedon Collection Box Listing acts as a finding guide to the content of the collection. It provides detailed information of the content, such as titles to publications, authors, dates of publications, and helpful notes for identification.